Structure formation and wear resistance of TiN-Ni ESA coatings after solar irradiation treatment - Paustovsky, A.V.; Frolov, G.A.; Timofeyeva, I.I.; Novikova, V.I.; Tsyganenko, V.S.; Mordovets, N.M.; Kostenko, A.D.; Isayeva, L.P. (Functional Materials, 2005)
It has been shown that the emitting ability of TiN electric spark coatings increases in 1.5 time after treatment by concentrated solar irradiation. This is effective for the use in friction pairs of mechanisms in outer space. The concentrated solar energy treatment of TiN-Ni spark coatings increases in 2-3 times the wear resistance due to oxide phase formation in the alloyed layer. The structure of steel 45 changes in the area of concentrated solar radiation action from the ferrite-pearlite to troostite with grain refining and hardness increase. The spark coating of 60 %TiN + 40 %Ni has been found to have optimum frictional and physical-mechanical properties. Показано, что в электроискровых покрытиях из TiN при добавлении Ni после обработки концентрированным солнечным излучением излучательная способность увеличивается в 1,5 раза, что эффективно при использовании в узлах трения механизмов в космическом пространстве. Применение концентрированной солнечной энергии для обработки ЭИЛ-покрытий из TiN-Ni повышает износостойкость покрытий в 2-3 раза вследствие образования оксидной фазы в легированном слое. В стали 45 в зоне воздействия концентрированной солнечной энергии происходят структурные изменения от ферри-то-перлита до троостита с измельчением зерна и повышением твердости. Установлено, что оптимальными триботехническими и физико-механическими свойствами и излучательной способностью обладает электроискровое покрытие из материала 60 %TiN + 40 %Ni. Показано, що у електроіскрових покриттях з TiN при додаванні Ni після обробки концентрованим сонячним випромінюванням випромінювальна здатність збільшується у 1,5 раза, що є ефективним при використанні у вузлах тертя у космічному просторі. Застосування концентрованої сонячної енергії для обробки ЕІЛ-покриттів з TiN-Ni підвищує зносостійкість покриттів у 2-3 рази, внаслідок утворення оксидної фази у легованому шарі. У сталі 45 у зоні дії концентрованої сонячної енергії відбуваються структурні зміни від ферито-перліту до трооститу із подрібненням зерна та підвищенням твердості. Встановлено, що оптимальні триботехнічні і фізико-механічні властивості має електроіскрове покриття з матеріалу 60 % TiN + 40 %Ni.